Polysemous particles in ancient Greek : a study with special reference to mīn and dī - Thijs, Kees (Language of classical literature,, 2025)
Anyone reading an Ancient Greek text will notice the abundance of pragmatic particles (e.g. ἄρα, γάρ, γε, δέ, δή, μέν, μήν, οὖν), a much-debated and challenging class of expressions. What are their semantic contributions, and how should we account for their notorious polyfunctionality? In this book, Kees Thijs provides a state of the art of modern particle theory, which he then applies to two of the most versatile Greek particles, μήν and δή. Using a diachronically oriented polysemy approach and a large-scale, varied research corpus, Thijs offers a new, unified account that significantly improves on both traditional handbooks (e.g. Denniston) and more recent particle studies.